Howard-von Recum family papers - Howard, Henry, Sir, 1843-1921.; Von Recum, Marie Ernestine Howard, Baroness, 1868-1954.
Diaries and correspondence relating primarily to the diplomatic career of Sir Henry Howard and documenting his postings in China; Denmark; France; Greece; Guatemala; Hague, Netherlands; Russia; the United States; and the Vatican during World War I. Includes correspondence and diaries, interleaved with photographs, clippings, and ephemera, of his daughter, Marie Ernestine Howard von Recum (also known as Da) pertaining to her years as a teenager posted with her family to various countries, her marriage to the German aristocrat Baron Rudolf von Recum, and world events such as World War I. Subjects also include the separation of family members on different sides during World War I and World War II and the lives of interrelated British, French, and German aristocrats. Correspondents include Sir Henry Howard's wife, Lady Cecilia Riggs Howard; their children, Alice Lawrason Howard, George Howard, Henry Mowbray Howard (also known as Pompey), and Janet Madeleine Cecilia Howard (also known as Jessie); Franz von Recum; Alice L. Riggs; Jane Agnes Riggs; and other members of the Howard, Riggs, and von Recum families.
Members of the Howard family and von Recum family including Sir Henry Howard, British diplomat, and his daughter, Marie Ernestine Howard von Recum.
Collection material in English, French, and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Howard, Alice Lawrason, -- 1876-1942 -- Correspondence; Howard, Cecilia Riggs, -- Lady, -- 1844-1907 -- Correspondence; Howard, George, -- 1869-1919 -- Correspondence; Howard, Henry Mowbray, -- 1873-1953 -- Correspondence; Howard, Janet Madeleine Cecilia, -- 1871-1960 -- Correspondence; Riggs, Alice L., -- 1840-1927 -- Correspondence; Riggs, Jane Agnes, -- 1854-1930 -- Correspondence; Von Recum, Franz, -- 1906-1974 -- Correspondence; Von Recum, Rudolf Heinrich, -- Baron, -- 1861-1944.; Howard family; Riggs family; Von Recum family; Aristocracy (Social class) -- France; Aristocracy (Social class) -- Germany; Aristocracy (Social class) -- Great Britain; Diplomatic and consular service, British; World War, 1914-1918.; World War, 1939-1945.; Catholic Church -- Foreign relations -- Great Britain; China -- Foreign relations -- Great Britain; Denmark -- Foreign relations -- Great Britain; France -- Foreign relations -- Great Britain; France -- Social life and customs -- 19th century; Germany -- Social life and customs -- 19th century; Great Britain -- Foreign relations -- Catholic Church; Great Britain -- Foreign relations -- China; Great Britain -- Foreign relations -- Denmark; Great Britain -- Foreign relations -- France; Great Britain -- Foreign relations -- Greece; Great Britain -- Foreign relations -- Guatemala; Great Britain -- Foreign relations -- Netherlands -- Hague; Great Britain -- Foreign relations -- Russia; Great Britain -- Foreign relations -- United States; Great Britain -- Social life and customs -- 19th century; Great Britain -- Social life and customs -- 20th century; Greece -- Foreign relations -- Great Britain; Guatemala -- Foreign relations -- Great Britain; Hague (Netherlands) -- Foreign relations -- Great Britain; Russia -- Foreign relations -- Great Britain; United States -- Foreign relations -- Great Britain; Diplomats